Un acercamiento a las políticas españolas de comercio y de inversión dirigidas a los países en desarrollo. Las políticas activas - Carballo Ríos, Felipe (Revista Española de Desarrollo y Cooperación, 2023)
The eighth of the Millenium Development Goals urges the governments of developed countries to increase the quantity and the quality of the ODA. Once celebrated the Millenium Summit + 5, the last meeting of G8 in Edinburgh, and waiting for the celebration of the Inter-ministerial Conference of the WTO in Hong Kong, the present article describes the evolution of the spanish policies of trade and investment with regard to the least developed and highly indebted countries. With a critical vision of the links and uses of some development instruments managed under formulas of exports support and to investment in these countries, the article offers a better comprehension of some of the active spanish policies developed in the last decades.